Barrierearme Textproduktion und Online-Darstellung mit OS-APS - Baumgartner, Dominik; Bösendörfer, Sarah; Borchert, Carsten (o-bib. Das offene Bibliotheksjournal, 2025)
Dies ist ein Praxisbericht zur Entwicklung und den Funktionen des OS-APS Readers. Der OS-APS Reader wurde im Rahmen des Projektes OS-APS STEMO entwickelt. OS-APS ist eine Open Source Academic Publishing Suite, deren Single Source Workflow um das Feature eines eigenen Readers erweitert wurde. Der OS-APS Reader kann wissenschaftliche Publikationen intuitiv, barrierearm und medienneutral darstellen
Keywords: Single Source Publishing; XML-Workflow; Barrierefreiheit

Elicitation Of Requirements and Development of Production Workflows for Accessible Diamond Open Access Publications - Baumgartner, Dominik; Bösendörfer, Sarah; Betz, Caroline; Prestel, Phillip; Eichler, Frederik; Borchert, Carsten (ABI-Technik, 2025)
As accessibility requirements impact scholarly communication, Diamond Open Access (DOA) publishing faces specific challenges in meeting compliance and technical standards while having limited budgets. This article examines how accessibility can be integrated into DOA workflows through the use of single-source publishing. Drawing on a requirements analysis conducted within the OS-APS, this paper outlines a framework for embedding accessibility features, from metadata handling and alt-text integration to responsive output formats, into a streamlined publication suite. Legal mandates (e.g., European Accessibility Act), technical standards (e.g., PDF/UA, WCAG), and stakeholder feedback shaped the design of OS-APS. The project identified and implemented key accessibility functions such as structural tagging, language detection, and an accessible reader. OS-APS exports now support PDF/UA, HTML, EPUB, and XML outputs. While some limitations remain, particularly in AI-assisted alt-text generation, this paper presents a viable and promising model for integrating accessibility “by design” into DOA publishing workflow
Keywords: Accessibility; Diamond Open Access; Single Source Workflow

Gottfried, Thomas / Zierer, Klaus: Ehrfurcht vor Gott. Über das wichtigste Bildungsziel einer modernen Gesellschaft - Baumgartner, Dominik (2025)